2007
DOI: 10.1115/1.2805445
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Signature Analysis as a Medium for Fault Detection: A Review

Abstract: Rolling element bearings find widespread domestic and industrial application. Defects in bearing unless detected in time may lead to malfunctioning of the machinery. Different methods are used for detection and diagnosis of the bearing defects. This paper is intended as a tutorial overview of bearing vibration signature analysis as a medium for fault detection. An explanation for the causes for the defects is discussed. Vibration measurement in both time domain and frequency domain is presented. Recent trends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 61 publications
0
51
0
1
Order By: Relevance
“…For an undamaged bearing the Kurtosis is typically 3 while greater values are normally associated with loss of integrity. However, the main drawback of using this method is that the Kurtosis begins to revert back to the undamaged value as the defect further develops [1,2]. Other statistical features such as the KolmogorovSmirnov statistic has been applied by several investigators [3,4] in which they reported success in diagnosing a damaged bearing.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For an undamaged bearing the Kurtosis is typically 3 while greater values are normally associated with loss of integrity. However, the main drawback of using this method is that the Kurtosis begins to revert back to the undamaged value as the defect further develops [1,2]. Other statistical features such as the KolmogorovSmirnov statistic has been applied by several investigators [3,4] in which they reported success in diagnosing a damaged bearing.…”
Section: Introductionmentioning
confidence: 95%
“…Other statistical features such as the KolmogorovSmirnov statistic has been applied by several investigators [3,4] in which they reported success in diagnosing a damaged bearing. Frequency domain analysis for machine fault diagnosis is well established and the authors refer the readers to a review by Patil et al [2].…”
Section: Introductionmentioning
confidence: 99%
“…The time domain approach includes the investigation of time wave form indices, probability density form, and probability density moments. The kurtosis calculated from probability density moments is one precursor parameter that is more sensitive to the early stage of bearing defects than the other time domain approaches due to its mathematical nature (Patil et al 2008). The frequency domain approach permits the detection of faults and the diagnosis of the health of a fan by comparing the vibration spectrum from the measurement to the characteristic defect frequencies.…”
Section: Published Studiesmentioning
confidence: 99%
“…Commonly used technique for fault detection is vibration-based signature analysis. Signal processing in vibration-based monitoring of rotating machinery offers very important information about anomalies formed internally in the structure of the machinery [6]. Hundreds of papers in this field, including theory and practical applications, appear every year in academic journals, conference proceedings and technical reports.…”
Section: Introductionmentioning
confidence: 99%